Dampak Film Animasi Upin Ipin Terhadap Sikap Peduli Lingkungan Siswa Kelas 5 Sekolah Dasar - Ayunda Rizki Safitri; Murtono Murtono; Deka Setiawan (WASIS : Jurnal Ilmiah Pendidikan, 2022)
The purpose of this study was to analyze the impact of the animated film Upin and Ipin on the environmental care attitude of 5th graders at SD 2 Ngarus.The research method used is qualitative phenomenology. This research is focused on looking at the impact of the film Upin and Ipin on students' environmental care attitudes. The research was conducted at SD 2 Ngarus. The informants in this study were 5th graders. The data collection techniques used were 1) documentation; 2) interview; and 3) observation. In analyzing qualitative data, it is carried out through three stages, namely: data reduction, data display, and conclusion drawing/verification.The results of the study found that there were changes in attitudes such as diligently helping and paying attention to plants and throwing garbage around them, turning off the water faucet when not in use, throwing garbage in its place after the informants watched the Upin and Ipin movie. Furthermore, the informants have awareness in recycling waste into items that have a selling value, use plastic waste after it is disposed of, invite friends to collect used items and then bury them.Meanwhile, the negative impact is that the informants never help their parents burn the accumulated garbage, the informants have not been able to save fuel (energy), and the informants sometimes do not throw away used goods.